Diversity in S-layers. (January 2017) - Zhu, Chaohua; Guo, Gang; Ma, Qiqi; Zhang, Fengjuan; Ma, Funing; Liu, Jianping; Xiao, Dao; Yang, Xiaolin; Sun, Ming
Abstract: Surface layers, referred simply as S-layers, are the two-dimensional crystalline arrays of protein or glycoprotein subunits on cell surface. They are one of the most common outermost envelope components observed in prokaryotic organisms ( Archaea and Bacteria ). Over the past decades, S-layers have become an issue of increasing interest due to their ubiquitousness, special features and functions. Substantial work in this field provides evidences of an enormous diversity in S-layers. This paper reviews and illustrates the diversity from several different aspects, involving the S-layer-carrying strains, the structure of S-layers, the S-layer proteins and genes, as well as the functions of S-layers.